2008
DOI: 10.4161/cbt.7.6.5910
|View full text |Cite
|
Sign up to set email alerts
|

Application of combination of short hairpin RNA segments for silencing VEGF, TERT, and Bcl-xl expression in laryngeal squamous carcinoma

Abstract: Results: We demonstrated that a recombinant plasmid containing multiple shRNAs could effectively and simultaneously inhibit VEGF, TERT and Bcl-xl mRNA and protein expression in the HEp-2 cells; the plasmid containing the 3 different shRNAs exhibited a potent antitumor effect on LSCC both in vitro and in vivo, and could much more effectively induced cell apoptosis than each single shRNA. We also demonstrated that the simultaneous blockage of these 3 genes have a better inhibitory effect on human HEp-2 cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
5
10
0
Order By: Relevance
“…19 Hong et al 20 have found that simultaneous C-myc and stat3 gene silencing is better than single C-myc or stat3 gene silencing in inhibiting growth and proliferation of melanoma cella. Yan Wang et al 21 has found that three-gene silencing is better than single gene silencing in inhibiting Hep-2 cell growth and proliferation, which is consistent with our results. In this study, reverse transcriptase PCR and western blotting indicated that mRNA and protein of the four genes were all decreased after simultaneous four-gene silencing, demonstrating that constructed plasmids can simultaneously inhibit the four target genes.…”
Section: Discussionsupporting
confidence: 93%
“…19 Hong et al 20 have found that simultaneous C-myc and stat3 gene silencing is better than single C-myc or stat3 gene silencing in inhibiting growth and proliferation of melanoma cella. Yan Wang et al 21 has found that three-gene silencing is better than single gene silencing in inhibiting Hep-2 cell growth and proliferation, which is consistent with our results. In this study, reverse transcriptase PCR and western blotting indicated that mRNA and protein of the four genes were all decreased after simultaneous four-gene silencing, demonstrating that constructed plasmids can simultaneously inhibit the four target genes.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the ratios of liver cancer cell growth inhibition and apoptosis in the β-catenin and STAT3 co-transfection group were significantly greater than those in the groups transfected with β-catenin or STAT3 siRNA alone. Similar to the results of the present study, simultaneous silencing of vascular endothelial growth factor, telomerase reverse transcriptase and Bcl-extra large expression improved the inhibition of cell growth and promotion of apoptosis in laryngeal squamous carcinoma (30).…”
Section: Discussionsupporting
confidence: 79%
“…Inhibiting the functions of the key genes of several pathways together is expected to achieve improved results for the purpose of cancer therapy (30). In agreement with this hypothesis, it was demonstrated that silencing β-catenin and STAT3 genes together led to enhanced cell apoptosis and loss of cell viability of HCC cells as compared with silencing of β-catenin and STAT3 genes individually.…”
Section: Discussionsupporting
confidence: 70%
“…As knockdown of Tert or Terc significantly reduces tumor growth,37,38 telomerase-targeting drugs may be an alternative to drugs that target telomeres.…”
Section: Drugs Targeting Telomerasementioning
confidence: 99%